2008
DOI: 10.1172/jci34957
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in thrombosis in mice are mediated by sex-specific growth hormone secretion patterns

Abstract: Sex differences in thrombosis are well described, but their underlying mechanism(s) are not completely understood. Coagulation proteins are synthesized in the liver, and liver gene expression is sex specific and depends on sex differences in growth hormone (GH) secretion -males secrete GH in a pulsatile fashion, while females secrete GH continuously. Accordingly, we tested the hypothesis that sex-specific GH secretion patterns cause sex differences in thrombosis. Male mice were more susceptible to thrombosis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 62 publications
3
47
0
Order By: Relevance
“…For instance, sex-specific patterns in growth hormone secretion and aging-related changes in sex-steroid hormonal balance are associated with preferential accumulation of fat in the upper body, 27 and both have been also associated with coagulation and thrombosis. 28,29 In the present study, no such hormonal data were obtained, and therefore we cannot further determine their potential role. Other obesity-related sex-specific factors may, however, play a role as well.…”
Section: Discussionmentioning
confidence: 65%
“…For instance, sex-specific patterns in growth hormone secretion and aging-related changes in sex-steroid hormonal balance are associated with preferential accumulation of fat in the upper body, 27 and both have been also associated with coagulation and thrombosis. 28,29 In the present study, no such hormonal data were obtained, and therefore we cannot further determine their potential role. Other obesity-related sex-specific factors may, however, play a role as well.…”
Section: Discussionmentioning
confidence: 65%
“…Recently, Wong et al (31) reported that substantial sexrelated differences in thrombosis in mice are mediated by sex-specific pulsatile or continuous secretion pattern of growth hormone. Similar to their observations, our animal study with GH given in a pulsatile manner showed no obvious sex differences in induction of hFIX expression from -802(-20A)FIXm1, while continuous GH infusion still remains to be tested.…”
Section: Resultsmentioning
confidence: 99%
“…Functionally, female platelet isolates, though capable of binding more fi brinogen and displaying a greater maximal aggregation extent than male platelet isolates (Leng et al , 2004 ;Bailey et al , 2009 ), actually do not aggregate as quickly as the larger number of male platelets do, thus to some degree rendering females less susceptible to thrombosis. In the absence of estradiol in acyclicity, female platelets are again more susceptible to thrombosis (Wong et al , 2008 ;Bailey et al , 2009 ). Platelets are indeed found to express ER β , which is hypothesized to have a direct effect on platelet function (Peters et al , 2002 ;Jayachandran and Miller , 2003 ;Bailey et al , 2009 ).…”
Section: Neuroprotectionmentioning
confidence: 98%
“…It is known that isolated female platelets bind more fi brinogen and have a greater maximal aggregation extent than male platelet isolates, and this platelet reactivity is altered in ovariectomized females (Leng et al , 2004 ;Bailey et al , 2009 ). Males have been shown to have higher platelet counts and faster clotting times than their female counterparts, thus making them more susceptible to thrombosis -possibly due to the differences in growth hormone secretion between the sexes (pulsatile in males, sustained in females), which in turn infl uence protein production of coagulation and thrombosis regulators (Wong et al , 2008 ;Bailey et al , 2009 ). Isolates of male rat platelets have been shown to display greater maximal aggregation in vitro than platelets isolated from female rats; this aggregation is reduced in male rats that have undergone castration (Emms and Lewis , 1985 ;Bailey et al , 2009 ).…”
Section: Thrombosismentioning
confidence: 99%
See 1 more Smart Citation